Mauritius - Cleary, Tim. (London : Kuperard ; New York : Distributed in the United States and Canada by Random House, 2011)
Culture Smart! Mauritius is an illuminating and practical guide to Mauritian culture and society. It will help you turn your visit-whether it's for business or for pleasure-into a memorable and enriching experience. Contents include: Local customs and traditions, the impact of history, religion, and politics, the Mauritians at home, work, and play, eating and drinking, Mauritian style, dos, don'ts, and taboos, business practices, communication, spoken and unspoken, and many practical tips for managing the unexpected.
"The essential guide to customs and culture"--Cover.
Includes bibliographical references (page 165) and index.
Keywords: Etiquette -- Mauritius; National characteristics, Mauritian; Mauritius -- Social life and customs -- 21st century; Mauritius -- Civilization; Mauritius -- Guidebooks